(untitled) (CIPEEX, 2025)
This document outlines the initial phases of a software engineering project aimed at developing a comprehensive client and employee registration system for a dental consultancy. The primary objective is to create an efficient and user-friendly platform that will streamline the management of client and employee information, improving overall operational efficiency. The project methodology includes the construction of detailed prototypes, alongside gathering and analyzing requirements to ensure the system is tailored to the specific needs of the consultancy. By incorporating feedback from stakeholders, the system is being refined to enhance usability and functionality. The preliminary results are promising, as the initial prototypes have been developed and are currently undergoing testing. Feedback from these tests is being actively collected and integrated into the design process. The conclusions emphasize the critical role of ongoing requirement analysis and iterative prototyping to ensure the system meets both current and future needs. This iterative approach will help refine the system’s overall performance, functionality, and user experience.